Penerapan Faktor Ergonomi pada Laboratorium Komputer STMIK Sumedang Dalam Menunjang Kenyamanan Pengguna - Dani Indra Junaedi (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2021)
The Sumedang STMIK computer laboratory is used for various activities such as practical lectures which are part of learning, competency testing, training and other Tridharma Higher Education supporting activities. The high intensity of use requires that the computer laboratory has the readiness of facilities to support activities and provide comfort for its users or in other words must pay attention to ergonomic elements that cover various aspects of the work station and its environment. The application of ergonomics must cover all aspects related to objects, meaning that the Sumedang STMIK computer laboratory must pay attention to physical ergonomics which includes ergonomics related to human anatomy, cognitive ergonomics related to human mental processes, organizational ergonomics related to optimizing the sociotechnical system and environmental ergonomics, related to lighting, temperature and noise. This research resulted in the recommendation of ergonomics standards that must be applied at the Sumedang STMIK Computer Laboratory along with the assessment form to be used. Periodically the ergonomics assessment needs to be done to adjust the conditions that have the possibility to change from the standard. After ensuring that the laboratory meets the ergonomics standards, a user satisfaction survey can be conducted on the comfort of the Sumedang STMIK computer laboratory